A measurement of the effectiveness and efficiency of pre-disaster debris management plans. (April 2017) - Crowley, Julia
Highlights: Measuring the effectiveness and efficiency of pre-disaster debris management plans. Surveys were distributed to counties with recent major disaster declarations. Counties with pre-disaster debris management plans were found to be more effective. Counties with pre-disaster debris management plans were partially more efficient. Abstract: Disaster debris management operations make up a significant portion of recovery expenses. The following study aims to examine how the presence of a plan makes disaster debris management effective and efficient. Ninety-five counties in the United States who received major disaster declarations between 2012 and 2015 were surveyed to examine the quality of their debris management processes. Forty-nine of these counties had debris management plans while forty-six did not. Statistical tests were conducted to address discrepancies in the effectiveness and efficiency of the debris management processes between the two groups. Such tests suggest that counties with pre-disaster debris management plans were more effective. These counties recycled almost twice as much disaster debris as counties without plans, and received over three times as much Public Assistance from the Federal Emergency Management Agency (FEMA). Counties with plans also reported higher levels of perceived preparedness for future debris challenges than counties without plans. Overall, counties with pre-disaster debris management plans were partially more efficient than counties without plans. They removed more cubic yards of debris per day, but there were no statistically significant differences between the two groups in the volume of debris removed per dollar.